DEFAULT IN UNSECURED DEBT AND RECEIVABLES AGREEMENT (WANPRESTASI DALAM PERJANJIAN UTANG DAN PIUTANG TANPA JAMINAN) - SIREGAR, DAHRIS (Ganec Swara, 2025)
Through a debt and receivables agreement between a lender and a loan recipient, a debt and receivables agreement can be created with anyone who has the capacity for it, not only financial institutions. By examining information obtained from the study of literature, books, papers, and laws and regulations regarding the problems discussed, normative research methodologies are used in this study. Primary, secondary, and tertiary data were used in this study. The study’s findings lead to the conclusion that the civil procedure legislation governs default settlements, just like it does for the settlement of other civil matters. This means that in the process of settlement, damages or collateral seizure may be imposed if necessary. This study’s goal is to determine the repercussions of a breach in an agreement involving unsecured debt and receivables as well as the process that was employed to fix the issue. Intentionality and weakness of faith are factors that cause a breach of a covenant. Without guarantee, default in a debt and receivables agreement can be settled both in court and out of court